2006
DOI: 10.1155/2006/974810
|View full text |Cite
|
Sign up to set email alerts
|

Expression Pattern of a Homeotic Gene, HOXA5, in Normal Breast and in Breast Tumors

Abstract: Introduction: Homeotic (HOX) gene products are now known to be functionally associated with breast cancer biogenesis. Recent evidence has indicated that HOXA5 regulates both p53 and progesterone receptor expression levels in breast cancer cells. In addition, HOXA5 has been shown to interact and regulate the activity of another protein referred to as Twist. As homeotic genes play a pivotal role in development, we sought to decipher the expression pattern in both normal breast tissues and in breast carcinomas. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 39 publications
0
8
0
2
Order By: Relevance
“…Henderson et al . reported that HOXA5 protein expression levels in breast carcinomas inversely correlated with EGFR expression [ 21 ]. Bruhl et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Henderson et al . reported that HOXA5 protein expression levels in breast carcinomas inversely correlated with EGFR expression [ 21 ]. Bruhl et al .…”
Section: Discussionmentioning
confidence: 99%
“…The binding of EGF to EGFR leads to receptor dimerization, autophosphorylation and the activation of several downstream signaling pathways, such as the MAPK pathway and the PI3K/Akt pathway, which play roles in cell proliferation, motility, and survival [ 19 ]; these pathways have also been shown to contribute to the abnormal growth of several types of human cancers [ 20 ]. Recent reports have demonstrated that HOX genes play a role in the regulation of several RTK family members, including EGFR [ 21 ], IGF1-receptor [ 22 ], and Eph-receptor [ 23 , 24 ], during development. Moreover, EGFR activation has been reported to stimulate HOXA7 expression [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…HOX genes are a group of essential regulatory genes that normally control embryonic development and that should be in the silenced state in the adult central nervous system [ 11 - 13 ]. Recent studies have shown evidence of the aberrant expression of HOX genes in diverse cancers, including gliomas [ 14 - 18 ]. Although solid evidence exists concerning the role of HOX genes in oncogenesis and therapeutic resistance in gliomas, the exact mechanism remains unclear, and only a small number of recent studies have been published [ 9 , 10 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 70% of breast cancer decreased HOXA5 protein levels when compared to normal breast tissues. However, the survival rate amongst the different low levels of HOXA5 expressing breast tumors was not significant 36 . Not only in breast cancer, Kim et al found that there was no influence of HOXA5 methylation on survival in all NSCLC or at stages II-IV.…”
Section: Discussionmentioning
confidence: 89%